Carbon Dioxide Emissions Control in the Electricity Sector: A General Equilibrium Analysis - Okpala, Chinweike Maryjane (Université d'Ottawa | University of Ottawa, 2013)
This paper assesses the potential aggregate and sectoral impacts of a carbon dioxide emissions control in the Canadian electricity sector using a carbon tax as policy instrument. A multisector static general equilibrium model of the Canadian economy is developed, using 2009 as base year. Three different electricity generation types (Coal-based, other-fossil-fuels-based and non-fossil-fuel-based) are considered along with the other industries in the economy. Several simulations with different carbon tax levels and two revenue recycling methods are considered. In addition to the traditional lump-sum transfer of the carbon tax revenue to the households, the study also analyses the impact of rebating the proceeds to the electricity sector while giving more credits to clean electricity production. The simulation results suggest that rebating the carbon proceeds to the producers entails a lower welfare cost in comparison to its transfers to households.